PRESERVING THE TINGUIAN CULTURAL HERITAGE: MOTHER TONGUE-BASED MULTI-LINGUAL EDUCATION AS TOOL - Elizabeth Valera (Lembaga Penelitian Universitas Pasundan, 2016)
Cultural heritage is important to people’s identity and character.Preserving the culture is therefore very important for the future generations. The Tinguians who are the natives of Abra Province have their own culture which is distinct from other Filipino ethnolinguistic groups. Studies on the Tinguians however, show that many of their customs, traditions, practices and beliefs are no longer observed or done. To develop socio-cultural awarenesswhich enhances the pride of the learner’s heritage, language and culture,the Department of Education has institutionalized the Mother Tongue-Based Multilingual Education as its fundamental educational policy and program. This study which is a qualitative research aimed to determine how the program helps in the preservation of the Tinguian culture. The interview guide was used to gather data from the teachers, and officials of the selected public schools in Tinguian communities where the program was piloted.These were complemented by the observations of the researchers when they visited the schools. Based on the findings of the study, the first language or mother tongue of the learners is Ilocano thus the medium of instruction for kindergarten to Grade 3 is Ilocano; some of the teachers are not Tinguians and cannot speak the dialect; there is no working orthography of the Tinguian dialects; there are no available teachers guide, reading and instructional materialsin Tinguian; many of the learners whose parents are Tinguians speak Ilocano with their friends and classmates.